Parental Beliefs, Investments, and Child Development: Evidence from a Large-Scale Experiment - Pedro Carneiro; Emanuela Galasso; Italo Lopez Garcia; Paula Bedregal; Miguel Cordero (Institute of Labor Economics (IZA), 2019)
This paper experimentally estimates medium term impacts of a large-scale and low-cost parenting program targeting poor families in Chile. Households in 162 public health centers were randomly assigned to three groups: a control group, a second group that was offered eight weekly group parenting sessions, and a third group that was offered the same eight group sessions plus two sessions of guided interactions between parents and children focused on responsive play and dialogic reading. In spite of its short duration and intensity, three years after the end of the intervention, the receptive vocabulary and the socio-emotional development of children of families participating in either of the treatment arms improved (by 0.43 and 0.54 standard deviation, respectively) relative to children of nonparticipating families. The treatments also led to improvements in home environments and parenting behaviors of comparable magnitudes, which far outlasted the short duration of the intervention.
Keywords: H43; I10; I20; I38; 330; parenting; early childhood development